The Influence of Workload and Career Development on Turnover Intention - Audiah, Hilda; Adi, Agung Nugroho (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to analyze the effects of workload and career development on employee turnover intention at PT XYZ in the property sector. Design/Methodology/Approach – This study employs a quantitative explanatory research approach to examine the causal relationships between workload, career development, and turnover intention. Data were collected from 120 employees of PT XYZ, selected from a population of 217 employees. The research instruments were tested for validity and reliability, followed by classical assumption tests. The data were analyzed using multiple linear regression and hypothesis testing with IBM SPSS version 25. Findings – The results indicate that workload has a positive and significant effect on employee turnover intention, meaning that higher workload increases employees’ intention to leave the organization. Conversely, career development has a negative and significant effect on turnover intention, indicating that better career development opportunities can reduce employees’ intention to leave. Furthermore, workload and career development simultaneously have a significant effect on turnover intention. These findings emphasize the importance of managing workload and providing clear career development pathways to retain employees. Originality/Value: This research offers value by examining the combined influence of workload and career development on turnover intention using a comprehensive quantitative approach. The study also increases the strength of its findings by collecting data from a larger number of respondents than initially required. The results contribute original evidence that can guide organizations in designing strategies to reduce turnover intention and improve employee retention.